Cosmopolitan Responsibility - Heilinger, Jan-Christoph (De Gruyter, 2019)
The world we live in is unjust. Preventable deprivation and suffering shape the lives of many people, while others enjoy advantages and privileges aplenty. Cosmopolitan responsibility addresses the moral responsibilities of privileged individuals to take action in the face of global structural injustice. Individuals are called upon to complement institutional efforts to respond to global challenges, such as climate change, unfair global trade, or world poverty. Committed to an ideal of relational equality among all human beings, the book discusses the impact of individual action, the challenge of special obligations, and the possibility of moral overdemandingness in order to lay the ground for an action-guiding ethos of cosmopolitan responsibility. This thought-provoking book will be of interest to any reflective reader concerned about justice and responsibilities in a globalised world.